Investigation into the use of learning analytics in online learning at South Africa's higher education institutions - Molokeng, Palesa Maralitle (Department of Information Systems, 2022)
Teaching and learning have evolved over time as students desire to engage with technology as part of their learning process. Technological advances are introducing new possibilities for higher education institutions (HEIs). Developments in educational technologies as well as the need by HEIs to improve both the teaching and learning environment are contributing to the growth of learning analytics (LA). Research in LA has predominantly been exploratory in nature and a shift is needed for evaluative research that explores the impact and outcomes of LA on students, educators and the institution as a whole. Moreover, there is limited research on the use of LA at HEI in a South African context with most research focusing on the Global North and Australia. This study aimed to understand the state of LA at HEIs in South Africa (SA) by identifying barriers of use as well as future potential of the use of LA in informing decision making, predicting learner outcomes and improving the overall learning and experience. The study draws on the Technology-OrganisationEnvironment (TOE) framework and DeLone and McLean IS success model to develop a theoretical integrated model to understand the state of LA at HEI in order to gain insights on the barriers and drivers of use, as well as potential of more advanced LA at institutions. To meet the objective of the study and to test the model, data was collected by conducting semi-structured interviews with participants at four prominent HEIs in SA. It was important to have a diverse representaion of roles to gain a balanced view on the use of LA across institutions. A qualitative thematic analysis approach was used following a hermeanutic cycle in the analysis process. The outcome of the study showed that a big variety of data are currently being collected at HEIs within SA and the data is used for LA to varying degrees. These findings show that data is used for various decision-making purposes in order to improve learning and teaching. The data is also used to understand student behaviours in order to predict student outcomes and to meet student support needs. Barriers and challenges exist that have impacted the adoption of LA; these include technological, organisational and environmental challenges such as quality of systems, culture to use data and ethical concerns. Opportunities for more advanced use of LA also exist which are econcouraging institutions to prioritise LA initiatives in their drive of being more data-driven. The main contributions that this study makes is to bring an SA context to a growing field of research and implementation of LA. This study demonstrates the challenges that are unique to SA in the adoption of LA within an online learning perspective as well as highligting challenges that are similar to other global institutions.